Long-term regulation of genetically modified primary hematopoietic cells in dogs - Okazuka, Kiyoshi; Beard, Brian C; Emery, David W; Schwarzwälder, Kerstin; Spector, Michele R; Sale, George E; Kalle, Christof von; Kiem, Hans-Peter; Blau, C. Anthony (Molecular therapy, 2011)
We report long-term results from a large animal model of in vivo selection. Nine years ago, we transplanted two dogs (E900 and E958) with autologous marrow CD34+ cells that had been transduced with a gammaretrovirus vector encoding a conditionally activatable derivative of the thrombopoietin receptor. Receptor activation through administration of a chemical inducer of dimerization (CID) (AP20187 or AP1903) confers a growth advantage. We previously reported responses to two 30-day intravenous (i.v.) courses of AP20187 administered within the first 8 months post-transplantation. We now report responses to 5-day subcutaneous (s.c.) courses of AP20187 or AP1903 at months 14, 90, and 93 (E900), or month 18 (E958), after transplantation. Long-term monitoring showed no rise in transduced cells in the absence of drug. Retroviral insertion site analysis showed that 4 of 6 (E958) and 5 of 12 (E900) transduced hematopoietic cell clones persisted lifelong. Both dogs were euthanized for reasons unrelated to the gene therapy treatment at 8 years 11 months (E958) and 11 years 1 month (E900) of age. Three clones from E900 remained detectable in each of two secondary recipients, one of which was treated with, and responded to, AP1903. Our results demonstrate the feasibility of safely regulating genetically engineered hematopoietic cells over many years.